Overweight and obesity : a study among university students in Sarawak, Malaysia - Patricia Pawa, Pitil; Siti Raudzah, Ghazali (Taylor & Francis Group, 2022)
Overweight and obesity are on the rise throughout Asia, with Malaysia at the top of the list. However, the most recent data among young people, particularly university students in Asia, are scarce. This study aimed to report the prevalence of overweight and obesity among university students attending two public universities in Sarawak, Malaysia, based on demographic data that included their levels of study, gender, and age ranges. This is a crosssectional research approach, which surveyed 622 university students aged from 18 to 24 years enrolled in associate and bachelor’s degree study. A self-administered questionnaire was distributed via an online platform from March to November 2020. Body mass index (BMI) was calculated from the obtained self-reported body weight and height for body weight status adhering to the World Health Organisation (WHO) and Asian cutoff scales. Based on the WHO cutoff scale, the prevalence of overweight and obesity was 14.31% and 10.13%, respectively, which is lower than Asian cutoff scale prevalence, 22.19% and 16.88%, respectively. A high prevalence of overweight and obesity was noted among the study sample, particularly male students. Bachelor’s degree students recorded higher BMI than those at associate level. Age groups were prominent in the prevalence of overweight and obesity in males, but an exception in females. In conclusion, a high prevalence of overweight and obesity was observed in this study. This study provides valuable data that may be applied to devise strategic interventions at improving the health of university students.